Molecular basis of Leigh syndrome: a current look - Schubert Baldo, Manuela (2020)
Leigh Syndrome (OMIM 256000) is a heterogeneous neurologic disorder due to damage in mitochondrial energy production that usually starts in early childhood. The first description given by Leigh pointed out neurological symptoms in children under 2 years and premature death. Following cases brought some hypothesis to explain the cause due to similarity to other neurological diseases and led to further investigation for metabolic diseases. Biochemical evaluation and specific metabolic profile suggested impairment in energy production (OXPHOS) in mitochondria. As direct approach to involved tissues is not always possible or safe, molecular analysis is a great cost-effective option and, besides biochemical results, is required to confirm the underlying cause of this syndrome face to clinical suspicion. The Next Generation Sequencing (NGS) advance represented a breakthrough in molecular biology allowing simultaneous gene analysis giving short-time results and increasing the variants underlying this syndrome, counting over 75 monogenic causes related so far. NGS provided confirmation of emerging cases and brought up diagnosis in atypical presentations as late-onset cases, which turned Leigh into a heterogeneous syndrome with variable outcomes. This review highlights clinical presentation in both classic and atypical phenotypes, the investigation pathway throughout confirmation emphasizing the underlying genetic heterogeneity and increasing number of genes assigned to this syndrome as well as available treatment.